Genealogi Pendidikan Pesantren Studi Genealogi Syaikhona Kholil Bangkalan Madura - Zaini, M.; Mahsun, Mahsun (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2019)
Islamic Boarding School Genealogy in Bangkalan, Study of Genealogy of Syaikhona Kholil Bangkalan Madura. This article is the result of field research using a qualitative methodology, to answer questions: 1) How the development of pesantren in Bangkalan, 2) What is the understanding of social and intellectual genealogy of Syaikhona Kholil Bangkalan. The approach in this study, namely the sociological and historical approach, because in the translation using sociological and historical aspects. The sociological aspect is used to trace the symptoms and social causality that accompany the role of Shaykhona Kholil, while the historical approach is used to trace sources in the past, in the form of archives or documents. While the theory used in this study, is a combination of three theories, including: educational theory, leadership theory and genealogy theory Michel Foucault. Combined with these three theories, it can be simplified that education is an effort to explain the teaching and learning process, which combines the leadership and genealogical practices (creating scientific rigging), one of them by way of matchmaking.